The The Effects of Input Processing Instruction on The Acquisition of Expression of Giving and Receiving (Juju Hyougen) by the Indonesian Learners of Japanese - Arianty Visiaty; Nisrina Nur Fitriani (Chi'e: Journal of Japanese Learning and Teaching, 2023)
This study examines the effectiveness of learning the Japanese expression of giving and receiving by applying input processing instruction to Japanese learners of Indonesia at the intermediate level. This study was quantitative research using data obtained from four tests, namely pre-test (first test), post-test (second test), test after two weeks (third test), and test after five weeks (fourth test). The study's respondents are university students of Al Azhar in their third year at the Japanese language and culture department. Based on the results of the first and the second test, it can be said that learning the expression of giving and receiving the Japanese language that applies input processing instruction is effective. However, the comparison results of the first and second tests, second and third tests, and second and fourth tests show that the input exercise does not affect the respondents' ability after two weeks and five weeks after receiving treatment. The average score of respondents tends to decrease in the test after two and five weeks, so it can be said that the input processing instruction does not affect the acquisition of Japanese expressions of receiving and giving. This can be caused by the lack of opportunities to use Japanese expressions of receiving and giving and the lack of exposure to an input of these expressions in subsequent class activities and students' daily lives. Keywords : Pendidikan Bahasa Jepang Japanese Education JournalJapanese FolkloreLearning Japanese ExpressionJapanese Studies